Taqlid and Ijtihad (American Journal of Islam and Society, 1992)
The Lexical and Technical Meanings of TaqlidThe lexical meaning and structure of the word “taqlid” clearly indicate thenegative connotations surrounding its technical meaning as well as its retentionof much of the literal sense. The Arabic root q-ld comes from qald, which means”to twist or to twine.” As most necklaces were twined or braided, the word cameto refer to necklaces, and the active form of the verb (taqlid) to putting on anecklace. An example from early Arabic poetry uses taqlid in this sense:They placed on her (round her neck) amulets,To ward off evildoers and enviers.The same word is also used to refer to the marking made around the neckof an animal destined for sacrifice during hajj. In addition, a camel is said tobe “necklaced” (muqallad) when a rope is placed over its head and around its neck.In a less literal usage, this word has the sense of placing responsibility onan individual, as in “The sultan charged (q-I-d) someone with a duty,” as charginga person in such a manner resembles putting a necklace around hidher neck.Here, the one who accepts the responsibility is as one who wears a necklace.‘The classical~uh’di efine taqlid as one’s ”acceptanceo f another‘s madhhQbwithout knowing the other person’s justification.” (In this definition, Madhhabincludes everydung that fills within the purview of ijtihad.) Although the fuqaha’have defined the term in different ways, all agree that it signifies the acceptanceof and acting upon another‘s word without trying to substantiate it. In other words, ...